2016
DOI: 10.15171/ehem.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and modeling of fluoride concentrations in groundwater resources using an artificial neural network: a case study in Khaf

Abstract: Background: One issue of concern in water supply is the quality of water. Measuring the qualitative parameters of water is time-consuming and costly. Predicting these parameters using various models leads to a reduction in related expenses and the presentation of overall and comprehensive statistics for water resource management. Methods: The present study used an artificial neural network (ANN) to simulate fluoride concentrations in groundwater resources in Khaf and surrounding villages based on the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Magnesium oxide is an inexpensive catalyst with a high catalytic potential for degrading pollutants such as dyes or drugs [1][2][3]. Numerous studies have shown that magnesium oxide possesses high surface reactivity and strong surface alkalinity [4]. To improve the surface reactivity of magnesium oxide, its specific surface area can be increased by the preparation of nano-magnesium oxide or porous magnesium oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxide is an inexpensive catalyst with a high catalytic potential for degrading pollutants such as dyes or drugs [1][2][3]. Numerous studies have shown that magnesium oxide possesses high surface reactivity and strong surface alkalinity [4]. To improve the surface reactivity of magnesium oxide, its specific surface area can be increased by the preparation of nano-magnesium oxide or porous magnesium oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Their shared objective was to identify springs or areas of high productivity based on GIS data. Recent studies using neural networks to predict groundwater quality have estimated the concentrations of contaminants such as nitrate, fluoride, and salinity in the groundwater (Mohammadi et al., 2016; Sahour et al., 2020; Wagh et al., 2018). Despite successful estimation and mapping, the results did not target the specific end use of the resource or consider the groundwater quality in detail; instead, they set light criteria and focused on groundwater availability or concentration of a specific contaminant.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the parameters of soil and water is costly and time consuming. The prediction and simulation of these parameters using modeling, reduces the cost of water management (19). The HYDRUS-2D software has been developed to simulate the two-dimensional movement of water, heat and solvents in a porous medium and different humidity conditions.…”
Section: Introductionmentioning
confidence: 99%